Tube shunt coverage with gamma-irradiated cornea allograft (VisionGraft) - Ekici, Feyzahan (Clin Ophthalmol, 2015)
PURPOSE: To investigate the clinical outcomes of tube shunt coverage using sterile gamma-irradiated cornea allograft. PATIENTS AND METHODS: The Wills Eye Hospital Glaucoma Research Center retrospectively reviewed the medical records of 165 patients who underwent glaucoma tube shunt procedures using sterile gamma-irradiated cornea allograft (VisionGraft) between December 2012 and November 2013. Demographic characteristics, type of tube shunt, and position were noted. Complications were recorded at 1 day; 1 week; 1, 3, 6, and 12 months; and on the final postoperative visit. RESULTS: One hundred and sixty-nine eyes of 165 patients were included. The mean follow-up time was 4.8±3.5 (ranging from 1 to 16) months. There was no evidence of immunological reaction, infection, or exposure in 166 eyes (98.2%). Three eyes (1.8%) experienced graft or tube exposure within the first 3 postoperative months. Two of the cases had underlying diseases: bullous pemphigoid and chronic allergic conjunctivitis. CONCLUSION: Coverage of tube shunts using gamma-irradiated cornea allograft had a low exposure rate and was well tolerated. The graft can be stored long term at room temperature and has an excellent postoperative cosmetic appearance.